Government Policy in the Differentiation of Organization and Content of School Education in the Ukrainian Soviet Socialist Republic (Late 30-s – 80-s of the XX Century.): Historiography and Research Sources - Larisa Berezovskaya (Pedagogical Discourse, 2013)
In the article historiographical developments are analyzed, the sources of the investigated problem are systematized and classified − the state policy in the differentiation of organization and content of school education in the Ukrainian Soviet Socialist Republic (USSR) (end of 30th − 80th years of the XX century.). Historiography problems are displayed in groups (historical and pedagogical historiography − Ukrainian, Soviet and modern Russian; historiography of other sciences (history of Ukraine, branch management) and in certain periods.